Practice and long-term outcome of unprotected left main PCI: real-world data from a nationwide registry. Issue 1 (2nd January 2022) - Kayaert, Peter; Coeman, Mathieu; Hanet, Claude; Claeys, Marc J.; Desmet, Walter; De Pauw, Michel; Haine, Steven; Taeymans, Yves
Abstract: Background: Percutaneous coronary intervention (PCI) is increasingly performed in significant left main (LM) lesions. Left untreated, the prognosis is poor, but PCI and coronary bypass surgery (CABG) behold risks as well. Additional long-term outcome data might guide future treatment decisions. Methods: Between 2012 and 2019, all 6783 patients who underwent LM PCI were prospectively enrolled in a national registry. Patients with prior CABG or prior LM PCI, and patients presenting in cardiogenic shock or after out-of-hospital cardiac arrest were excluded. From the remaining 5284 patients, baseline and procedural data as well as long-term survival were assessed. Results: The annual rate of LM PCI increased from 422 (2.2% of PCIs) in 2012 to 868 in 2018 (3.0%). By 2018, 71% of the interventional cardiologists performed at least 1 LM PCI a year, though only 5 on average. Use of transradial access (TRA) in LM PCI increased from 20.4% in 2012 to 59.5% in 2019. All-cause mortality was 6.0% at 30 days and 18.5% at a mean follow-up of 33.5 months. Independent predictors of higher long-term mortality were older age, diabetes, multivessel disease, an urgent indication, a suboptimal angiographical result, and non-exclusive use of drug-eluting stents. TRAand higher operator and centre LM PCI experience were independent predictors of a lower long-term mortality. Conclusion: LM PCI is associated with high short- and long-term mortality. Use of TRA and higher expertise in LM PCI were associated with better survival.